1989
DOI: 10.3382/ps.0681088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Added Pigments, Salt, and Phosphate on Color, Extractable Pigment, Total Pigment, and Oxidation-Reduction Potential in Turkey Breast Meat

Abstract: Ground turkey breast meat treatments were prepared with 16 combinations of myoglobin (0, .4 mg/g meat), cytochrome c (0, .1 mg/g meat), salt (NaCl; 1, 2.5%), and sodium tripolyphosphate (0, .5%) before cooking to determine their effect on meat color, water extractable pigments, total pigment, and oxidation-reduction potential in cooked turkey breast meat Addition of myoglobin did not increase extractable pigment but significantly (P<01) increased the redness (a-value) and total pigment of cooked meat Cytochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…Contrary to our results, Ahn and Maurer (1989) found that under normal conditions, oxidation-reduction potential in meat decreases during postmortem storage.…”
Section: Discussioncontrasting
confidence: 56%
“…Contrary to our results, Ahn and Maurer (1989) found that under normal conditions, oxidation-reduction potential in meat decreases during postmortem storage.…”
Section: Discussioncontrasting
confidence: 56%
“…Results supported the observations of Schmidt and Trout (1984), who stated that at high pH levels (pH > 6.0) beef, pork, and turkey appeared inadequately cooked. Ahn and Maurer (1989) reported that the addition of phosphate significantly increased the "a" value and decreased the "L" value of cooked turkey breast meat.…”
Section: )mentioning
confidence: 98%
“…In another investigation, Osborn et al [2003] found that metmyoglobin and ferrichemochrome could be reduced to form the oxymyoglobin pigment (which is responsible for the pink colour) under reducing conditions with enzymatic or non-enzymatic reactions. In addition, the presence of sodium chloride, phosphate, and the increase of pH results in a decrease in lightness, and an increase in the pink colour of cooked meat [Ahn & Maurer, 1989;Brewer et al, 2001].…”
Section: Kinetic Data Of Colour Parametersmentioning
confidence: 99%